BIOLOGY, MORPHOMETRY, AND REPRODUCTIVE POTENTIAL OF MELON FRUIT FLY (Zeugodacus cucurbitae COQUILLETT) ON BITTER GOURD (Applied Biological Research, 2026)
The melon fruit fly, Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae), a major pest of cucurbits, is responsible for severe yield losses as well as trade restrictions due to its quarantine importance. The present study examined the biology, morphometry, and reproductive potential of Z. cucurbitae on bitter gourd (Momordica charantia) during two consecutive Kharif seasons (2023 and 2024) at OUAT, Bhubaneswar, Odisha (East & South Eastern Coastal Plain Zone) and ICAR-IIVR, Varanasi, Uttar Pradesh (Middle Gangetic Plains), respectively. Laboratory-reared populations were assessed for developmental duration across the life stages, their morphometric traits, adult longevity, female fecundity, and male: female ratio. Minor spatial variations in the developmental dynamics of Z. cucurbitae was attributable to differences in populations established from maggots collected from infested fruits in Bhubaneswar and Varanasi. At Bhubaneswar, the fruit fly had a total life span of 37.45 ± 3.05 days in males and 41.30 ± 2.32 days in females, whereas at Varanasi the life span lasted for 40.90 ± 1.84 days in males and 45.55 ± 3.06 days in females. The durations of embryonic, maggot, and pupal stages also showed minor locational variation between the two populations. Morphometric parameters, including egg, maggot, pupal dimensions and adult measurements (length and width) exhibited minor variation between locations, with females consistently larger than males. High fecundity (78-81 eggs female-1) and a slightly male-biased sex ratio (1.15-1.24:1) were observed at both the locations. The study demonstrated population-level developmental variability and phenotypic plasticity in Z. cucurbitae even under uniform laboratory conditions.
Keywords: Biology, bitter gourd, developmental duration, fecundity, morphometry, Zeugodacus cucurbitae